JSON quick syntax reference - Jackson, Wallace (Expert's voice in Web development., 2016)
This compact quick scripting syntax reference on JSON covers syntax and parameters central to JSON object definitions, using the NetBeans 8.1 open source IDE software package. The JSON Quick Syntax Reference covers the syntax used in the JSON object definition language, logically organized by topical chapters, and getting more advanced as chapters progress, covering structures and file formats which are best for use with HTML5. More specifically, you'll learn the following: " What is and how to use the Object Definition Syntax supported in JSON " What comprises a JSON content production workflow " What are the concepts and principles behind the JSON Object Definitions " How to use JSON code snippets and apply them in your web applications " How to utilize NetBeans, Android Studio and Eclipse IDEs for your JSON coding " What are and how to use the key factors regarding the data footprint optimization work process, the in-lining of .CSS and .JS files " And, why a data footprint optimization work process is important